Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I'm struggling with understanding why the following statement is true:

Let $X$ be a Random Variable with Poisson distribution. Let $Z$ be a Random Variable independent from $X$, whose distribution is $P(Z=0.9)=0.2=1-P(Z=0.6)$. Let $Y$ be a Random Variable such that $Y |( X=x , Z=z)\sim \text{Binom}(x,z)$.

Then given $Z=0.9, Y\sim \text{Poisson}$.

I'm told that it is a consequence of some general fact about split Poisson variables but I couldn't make much of that fact, or wasn't able to see why it's true by myself. I don't really know how to go about this so any help would be greatly appreciated.

Thanks!

share|improve this question

1 Answer 1

up vote 3 down vote accepted

To prove that the distribution of $Y$ conditional on $Z$ is Poisson, you could do the following \begin{eqnarray*} \Pr \left( Y = y|Z = z \right) & = & \sum_{x = y}^{\infty} \Pr \left( Y = y|Z = z, X = x \right) \Pr \left[ X = x \right]\\ & = & \sum_{x = y}^{\infty} \left( \begin{array}{c} x\\ y \end{array} \right) z^y \left( 1 - z \right)^{x - y} \frac{\lambda^x}{x!} e^{- \lambda}\\ & = & e^{- \lambda} z^y \lambda^y \frac{1}{y!} \sum_{x = y}^{\infty} \frac{\left\{ \left( 1 - z \right) \lambda \right\}^{x - y}}{(x - y) !}\\ & = & e^{- \lambda} z^y \lambda^y \frac{1}{y!} \underbrace{\sum_{w = 0}^{\infty} \frac{\left\{ \left( 1 - z \right) \lambda \right\}^w}{w!}}_{= e^{\left( 1 - z \right) \lambda}}\\ & = & e^{- z \lambda} \frac{\left( z \lambda \right)^y}{y!} \end{eqnarray*}

The first line comes from $\Pr \left( Y = y | Z = z, X = x \right) = 0$ for $y >x$ (One thousand thanks for Stefan Hansen for pointing that out). The second line comes from inputting the formulas for the binomial and Poisson probabilities and the fourth line comes from applying the change of variable the change of variable $w = x - y$. By the last line we conclude that $Y$ conditional on $Z = z$ is Poisson with parameter $\lambda z$.

share|improve this answer
    
That's it, thanks a lot for the detailed answer! –  Adar Hefer Jan 30 '13 at 13:44
    
@AdarHefer You're welcome. –  Learner Jan 30 '13 at 13:46
1  
Shouldn't your sum be from $x=y$, since $P(Y=y\mid Z=z,X=x)=0$ when $y>x$? –  Stefan Hansen Jan 30 '13 at 13:53
2  
@StefanHansen Thanks a lot for your correction. I amended my answer. –  Learner Jan 30 '13 at 14:08
    
Oh now the substitution looks more appropriate. Brilliant, thanks you guys! –  Adar Hefer Jan 30 '13 at 14:13

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.